RANCANGAN DAN IMPLEMENTASI SISTEM PENGARSIPAN DIGITAL BERBASIS WEB SEBAGAI DATA PENDUKUNG DALAM AKREDITASI PROGRAM STUDI (Studi Kasus: Fakultas Sains & Teknologi Universitas Respati Yogyakarta) - Sahal, Ahmad; Aini, Farida Nur (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2019)
The rapid development of science and technology can cover all aspects of life, including writing and writing, and can also store data in digital form in the form of storage media in the form of hard disks or the like. Besides that, it can also be found in a data storage system using a database system, which in this storage system makes it easy to get stored data whenever needed. The application developer scheme used for digital processing, uses the Rapid Application Development (RAD) method. Create a prototype built with Computer Aided Software Engineering (CASE) that allows, creates data models, converts data models to databases, and codes in one device, but will remain at this stage. From this study are the results of the design used to create digital archives, for the process of Digital Archive Implementation is in the process of completion. It is expected that there will be a process of implementing the Archive Elimination Process in the Study Program at the Faculty of Medicine and Technology at Respati University in Yogyakarta.